Participatory mapping of the natural domain and ecological and hydrologic survey in selected communities of Tinglayan, Kalinga - Alangui, Wilfredo V. (Animo Repository, 2009)
The participatory mapping and eological hydrologic survey of selected communities in TInglayan, Kalinga is a research project that was started in early 2007 and was motivated partly by reports of on-going negotiations for mining exploration in portions of Tinglayan and its neighboring municipalities and the possible construction of a geothermal plant within the said area. Tinglayan is a municipality in Kalinga whose terrestrial and inland water areas of biological importance are categorized as "extremely high" by the Philipine Biodiversity Conservation Priority-setting Program (PBCPP, 2002). The resources in this municipality, however, have never been systematically studied and surveyed. The general objectives of the study were to survey the geological and biological resources in the area and to generate resource maps based on the field data. It is an initial documentation of the natural resources in Tulgao West and Tulgao East, two of the communities that will be affected by the proposed mining exploration and operations of a geothermal plant. Results are meant to help these communities make informed decisions regarding development projects that could potentially impact negatively on the resources that they have protected and conserved for generations. The resulting database could also help the people plan for alternative development projects that are low-impact and can be directly managed and controlled by them. In terms of policy, this is UP Baguio's contribution to the enrichment of the Free Prior and Informed Consent (FPIC) process, the conduct of which has been continious from the point of view of the affected communities and other interested parties. The research output, though preliminary, is an important contribution in environmental benchmark, data generation and monitoring in the Cordillera region. Like in many places in the Cordillera region, the primary threat to the biodiversity of Tulgao's forests is land conversion. The research site was heavily disturbed by human activity (e.g. clearing of forests to give way to vegetable gardens resulting to forest gaps of variable sizes. However, even with the fragmentation that was observed in the area, and despite the limited scope covered in the survey, the results of this study indicate a rich and diverse ecosystem. This study may be seen as an initial Environmental and Social Impact Assessment (ESIA) that can immediately be used by the Tulgao communities, relevant agencies and government bodies to decide on whether a geothermal project should be implemented in the. The study concludes that safeguarding the integrity of the ecosystem in Tinglayan requires (1) The conduct of a biodiversity study in a bigger area and to include two montane forests, namely Mt. Mosimus and Mt. Binulauan, and (2) the initiation of community members in environmental monitoring A select group of residents (barangay leaders, teachers, high school or college students, for example) can be identified and trained as local researchers to measure environmental data , like rainfall, water temperature, water discharge; properly collect flora and fauna and undertake mapping. These are doable strategies considering the success of the strategy of sustained community participation employed in this just-concluded project.